Clinical relevance of emphysema in patients hospitalized with community‐acquired pneumonia: Clinical features and prognosis. (19th April 2021) - Seo, Hyewon; Cha, Seung‐Ick; Shin, Kyung Min; Lim, Jae Kwang; Lee, Won Kee; Park, Ji‐Eun; Park, Sunji; Choi, Sun Ha; Lee, Yong‐Hoon; Yoo, Seung‐Soo; Lee, Shin‐Yup; Lee, Jaehee; et al.
Abstract: Introduction: Few studies have investigated the influence of emphysema on clinical features of patients presenting with community‐acquired pneumonia (CAP). Objectives: The aim of this study was to examine the clinical and microbiological features of patients with both CAP and emphysema. Methods: This retrospective study included patients with CAP who underwent computed tomography (CT) scan at the time of presentation. Patients were allocated into emphysema and control groups, and clinical variables were compared between the two groups. The emphysema group was further divided into three subgroups (mild, moderate, and severe) according to the extent of emphysema on CT scan. The clinical variables of each subgroup were compared with the control group. Results: Of 1676 patients, 431 patients (25.7%) were classified into the emphysema group. CAP patients with emphysema were more likely to have a high CURB‐65 score and pneumonia severity index and a lower incidence of complicated parapneumonic effusion or empyema. The emphysema group exhibited longer hospital stay. In addition, 30‐day mortality in the severe emphysema group was significantly higher compared with the control group. As etiological agents, Streptococcus pneumoniae, Pseudomonas aeruginosa, Enterobacteriaceae, and multidrug‐resistant pathogens were significantly more common in the emphysema group compared with the control group. Conclusions: The presence of emphysema in CAP patients was associated with a more severe form of CAP, a longer hospital stay, and a lower incidence of complicated parapneumonic effusion or empyema. Moreover, CAP patients with severe emphysema exhibited higher 30‐day mortality than those without emphysema.